School dropout and participation on drug trafficking activities in Sonora, Mexico - Piña Osuna, Francisco Manuel (Acta Universitaria, 2021)
School dropout, understood as the permanent abandonment of studies, has been a factor linked to crime reproduction (Kessler, 2004; Reyes, 2012; Rojas, 2012). This study aims to describe the relationship between school dropout and participation in drug trafficking, considering the social control crime theory (Hirschi, 2003), which indicates that detachment from social structures, such as school, fosters transgression of individuals. Through interviews about school trajectories carried out with 11 prisoners for drug crimes in the state of Sonora, México, the findings show that school dropout made the informants’ working and economic conditions precarious, where drug trafficking was a means to overcome the economic lag. The findings allow to conclude the importance of recovering the idea of school training as a mechanism for social mobility.